The Impacts of Corporate Governance on Dividend Pay-out Ratio Policy before and during the Covid-19 Era: The study case in the Energy Industry in Indonesia - Laturette, Kazia; Hartono, Wendra; Gunawan, Kartikasari (AIBPM Publisher, 2023)
The purpose of this study is to analyze the impacts of good corporate Governance during the Covid -19 era on the dividend payout ratio policy in Indonesia. Moreover, during the Covid- 19 era has urged the higher management such US boards ofDirectors to deal with all difficulties and uncertainties in the business situation. During the Covid-19 era, the Energy has faced big challenges due to lock down policy occurred in many big areas which can leads to disruptive global economic supply chains. Due to the lock down, the number of demands for energy has decreased, henceforth the price is becoming more expensive. In this research will show and compare the conditions of the energy industry before and during the Covid-19 pandemic. this research is categorized quantitative research which the sample used is gathered from secondary data, financial reports, from basic material industry for publicly listed companies on the Indonesia Stock Exchange during 2018 – 2020, a total of 33 companies. Result of study This showing only the boards of Directors and Commissioners Independent before the pandemic took effect to dividends payout ratio